Description of Metopiellus painensis sp. nov. (Coleoptera, Staphylinidae), first troglobitic Pselaphinae from Brazil - Asenjo, Angélico; Ferreira, Rodrigo Lopes; Zampaulo, Robson De Almeida (Zootaxa, 2017)
Metopiellus painensis new species, of the Neotropical pselaphine tribe Metopiasini, is described from Pains region, Brasil (Minas Gerais). Major diagnostic features are illustrated and a key to the known species is given.